The Influence of Transformational Leadership and Innovative Work Behavior on Employee Performance - Ummi Saadah; Briyan Cadalora Putra; Ria Dini Apriliasari; Rr. Indah Permatasari (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examines the effects of transformational leadership and innovative work behavior on employee performance at PT. Cipta Niaga Semesta, an FMCG distribution company in Bojonegoro, East Java. A quantitative approach was used, involving all 50 employees as both population and sample through saturated sampling, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The results show that transformational leadership has a positive and significant effect on employee performance and on innovative work behavior, while innovative work behavior has no significant effect on employee performance. This implies that strengthening transformational leadership is a more effective lever for improving performance than innovative work behavior alone. The study is limited to a single company and a cross-sectional design, which restricts generalizability.